The Relationship between Social Media Consumption and Generation Z's Marriage Preference - Revalina Azzahra Lazuardi; Yogaprasta Adi Nugraha; Dwi Rini Sovia Firdaus; Toto Sugiarto (Jurnal Riset Komunikasi (JURKOM), 2026)
The widespread circulation of “fear of marriage” narratives on social media has intensified public discourse on intimate relationships and raised concerns about shifting marital perceptions among Generation Z. This study examines the relationship between social media exposure, perceptions of negative marriage-related issues, and marriage preferences among Generation Z. A quantitative descriptive approach was employed using accidental sampling. Data were collected from 390 undergraduate students from Universitas Pakuan, IPB University, and Universitas Ibn Khaldun in Bogor City, Indonesia, through a structured questionnaire with a four-point Likert scale. Descriptive statistics and Pearson correlation tests were applied. The findings reveal a weak but significant positive correlation between social media exposure and marriage preference (r = 0.164; p = 0.001), and a significant negative correlation between perceptions of negative issues such as domestic violence, financial burden, and infidelity and marriage preference (r = −0.238; p = 0.000). Notably, 95.92% of respondents reported positive marriage preferences. This study contributes to communication scholarship by demonstrating that social media does not reduce Generation Z’s intention to marry, but instead shapes more selective and rational marital decision-making within digital meaning-construction processes.